The making of curriculum collected essays - Goodson, Ivor 1945- (Studies in curriculum history, 1995)
This is the second edition of a book first published in 1988 in which Ivor Goodson explores a number of aspects of the 'invention' and promotion of the so-called traditional subjects. He describes the way the subjects develop over time to a point where they can be presented and promoted as 'academic' disciplines. He shows that the claim to be academic is in fact the result of a substantial political contest covering a century or more. The traditional subject is, in short, invented. Once we look at the political process of inventing, promoting and sustaining the school subject a very different perspective to that conventionally employed for understanding the school curriculum emerges. The 'traditional subjects' turn out to be a kind of politician's 'Piltdown man' and, once this is grasped, the existing discourse over the secondary school curriculum is seen in a very different light